2011
DOI: 10.1007/s10397-011-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

How time flies: a prospective analysis of theatre efficiency during elective gynaecology lists

Abstract: The aim of this study was to assess the time patients spend at the various stages of the surgical journey and identifying factors that lead to "bottlenecks". A prospective, observational study of 70 patients over 23 consecutive elective gynaecology lists. Timelines of patients' surgical journey were recorded and various outcomes such as room turnover and patient turnaround intervals calculated. Of the 70 patients (23 major and 47 intermediate), 32 were managed by one anaesthetist and 38 cases by two. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…At the same time, efforts should be made in order to minimize the consequences to the patients and optimize resources' usage in other ways. On one hand, patient turnover could be improved by monitoring the time needed by standard perioperative procedures and activities [ 7 , 8 , 20 ]. On the other hand, we should maybe rethink our context where productivity is increasingly measured in number of procedures rather than in health outcomes, particularly in the case of such complex disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, efforts should be made in order to minimize the consequences to the patients and optimize resources' usage in other ways. On one hand, patient turnover could be improved by monitoring the time needed by standard perioperative procedures and activities [ 7 , 8 , 20 ]. On the other hand, we should maybe rethink our context where productivity is increasingly measured in number of procedures rather than in health outcomes, particularly in the case of such complex disease.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the usage of the operating theatre (OT) is often under the spotlight of decision-makers [ 6 ]. In spite of evidence that a great proportion of the OT time is lost on nonsurgical activities [ 7 , 8 ], most surgeons have probably felt the pressure to finish a procedure at the planned time, victims of the belief that operative times are predictable. Our need for certainty makes it difficult to question the often wrong but somehow necessary prediction of surgical procedures duration, which is the basis for OT daily planning [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we defined start time as the time when the patient is transferred onto the theatre operating bed. Lewis et al [12] found that 91.3% of lists in a UK hospital started late, while locally in SA, Asmal et al [8] found that 74% of lists started late. Asmal et al [8] also defined theatre late starts as lists starting after 08h15.…”
Section: Researchmentioning
confidence: 99%